Performance Optimization of Endoreversible Simple MCBC Coupled to Variable-temperature Reservoirs Based on NSGA-Ⅱ Algorithm - Chenqi TANG; Lingen CHEN; Wenhua WANG; Huijun FENG; Shaojun XIA (发电技术)
Based on the previously established model of an endoreversible simple modified closed Brayton cycle (MCBC) coupled to variable-temperature reservoirs, the effect of parameters such as compressor pressure ratio on cycle performance was analyzed. The dimensionless power output and the dimensionless ecological function were optimized respectively by selecting cycle pressure ratio and the heat conductance distributions of heat exchangers as the design variables to optimize the performances of the endoreversible simple MCBC coupled to variable-temperature reservoirs. Finally, based on the NSGA-Ⅱ algorithm, the pressure ratio and the heat conductance distributions were optimized by taking the dimensionless power output, thermal efficiency and dimensionless ecological function as the optimization objectives, and the sensitivity of the related parameters was analyzed. The results show that there is a significant correlation between the inlet temperature ratios of the regular combustion chamber (RCC) and the converging combustion chamber (CCC) on the results of the single-objective optimization. It is found that compared with the results obtained by single-objective optimization, the optimal solutions corresponding to multi-objective optimization have smaller deviation indexes, and the deviation index is the smallest through Shannon entropy making. The sensitivity analyses show that the effects of the optimization variables changing within the range from -10% to 10% on the optimal dimensionless power output, the optimal thermal efficiency, the optimal dimensionless ecological function and its corresponding isothermal pressure drop ratio are very small, and the ranges do not exceed 5%.